Prescription patterns and drug utilization in respiratory tract infections: implications for antimicrobial stewardship at a tertiary care teaching hospital - Princy Domnic Dsouza; Sai Phalguna Prakash Chitralu; Chandrashekhar Mallikarjun Patil; Vinod Ashok Koujalagi; Sanatkumar Bharamu Nyamagoud (Monaldi Archives for Chest Disease)
Respiratory tract infections (RTIs) are common causes of hospital admissions and are often treated with multiple medications, including antibiotics, contributing to antimicrobial resistance. Effective drug utilization evaluation (DUE) is essential for ensuring rational drug use in RTI management. This study aimed to assess prescription patterns and drug utilization in RTI patients at a tertiary care hospital, focusing on the rationality of drug use, polypharmacy, adherence to clinical guidelines, and implications for antimicrobial stewardship. A cross-sectional study was conducted at Vivekananda General Hospital, Hubballi, India, from August 2023 to January 2024. Data from 200 RTI inpatients, including demographics, medication types, administration routes, and prescription patterns, were analyzed. Descriptive and inferential statistics were used to evaluate adherence to guidelines and rational drug use. DUE revealed that 50.99% of patients were not prescribed cough syrup. Oral (52%) and intravenous (48%) routes were the most common. Budesonide was the most frequently prescribed bronchodilator (26.49%), and 72.45% of patients received oxygen. Ceftriaxone (12.68%) and azithromycin (11.88%) were the most commonly prescribed antibiotics. A high prevalence of polypharmacy was identified, with 39.50% of patients receiving more than three antibiotics, raising concerns about drug interactions and rationality. The study underscores the need for stricter adherence to clinical guidelines and targeted antimicrobial stewardship in RTI management. Enhanced DUE practices could improve patient outcomes and promote rational drug use.